Neuromuscular degeneration. (17th October 2012) - Fisher, Caroline; Freris, Nicole
Abstract : After an angina attack, Mustafa Gunaydin was prescribed cholesterol lowering drugs, which seemed to trigger neuromuscular degeneration, culminating in his death. His story is told by his partner